ESTUDO DO GERENCIAMENTO DE RISCOS EM CONTRATOS DE CONCESSÃO RODOVIÁRIA - Piña, Ana Beatriz Souza; Viana, Vanessa Lequesteboumes Borges; Carvalho, Michele Tereza Marques (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Concessions are recurrent in the civil construction sector, especially in infrastructure works. One of the Brazilian sectors that most benefits from this form of contract is the road sector. Despite widespread use, managing the contractual risk of concessions is still an issue and promotes numerous disputes between contract stakeholders. This study focuses on the risk management used by the public regulatory agency of road concessions, aiming to position the maturity of the risk management of this agency and to compare risk allocation to other countries. This evaluation was carried out by analyzing the existing highway concession contracts, comparing the stages of Brazilian concessions among themselves and also with international references of the Mundial Bank. Also, ANTT maturity stage was established by the use of a maturity matrix. The reached conclusion is that although there was a maturity growth in the allocation and positioning of the risks along the national contracts, there is still no risk management being carried out by the public initiative, which promotes extra-official readjustments of toll prices and the accumulation of additives.